Polyamorphism and Two State Model in Liquid GeO\(_2\) under Compression: Insight from Visualization of Molecular Dynamics Data - Hong, Nguyen Van; Lan, Mai Thi; Nhan, Nguyen Thu (Communications in Physics, 2014)
The polyamorphism and two-state model based on the coordination number distribution in liquid GeO\(_2\) at 3200 K and in a wide pressure range are investigated by molecular dynamics simulation. Results show that the structure of liquid GeO\(_2\) mainly consists of GeO\(_x\) coordination units \((x=4,5,6)\) and OGe\(_y\) linkages \((y=2, 3)\). The distribution of OGe\(_y\) linkages in network structure is not uniform but tends to form clusters of OGe\(_y\). The cluster of OGe\(_2\) will form low-density phase region, conversely the cluster of OGe\(_3\) will form high-density phase region. In other word, under compression, in the liquid GeO\(_2\) coexist two states: low-density and high-density. The size of phase regions significantly depends on compression.